PENGARUH PROMOSI PENJUALAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA ALFAMART CABANG PLAOSAN 2 - Eigis Yani Pramularso (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of sales promotions and prices on purchasing decisions at Alfamart Plaosan branch 2. Collecting data using questionnaires distributed to buyers with a total of 96 respondents. The data processing technique was carried out using the SPSS 25 computer program to analyze the existing tests, namely in the form of multiple regression tests which were previously tested for validity, reliability, and classical assumptions. This study resulted in the findings that individually or jointly sales promotions and prices have a positive and significant effect on purchasing decisions. Sales promotions that are carried out need to be improved with variations in existing programs and price policies need to be considered in their determination so that buyers still feel confident that the existing prices are appropriate.